2017
DOI: 10.1002/adem.201600829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Shape on Texture Formation during Severe Plastic Deformation of Pure Copper

Abstract: In this study, the authors use a combination of electron backscattered diffraction and polycrystal plasticity modeling to study the effect of grain shape on texture development in high pressure torsion and high pressure double torsion in high purity Cu. With varying applied pressures and after a large amount of strain corresponding to two to four turns, the average aspect ratios of the grains has changed from being elongated under higher pressures to nearly equiaxed for lower pressures, while keeping the avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…To date, there have been a few number of studies investigating the effects of grain shape on texture evolution. Jahedi et al [28] conducted both experiments and the VPSC simulation approach introduced by Beyerlein et al [29] to study systematically the effect of grain shape on texture evolution during simple shear deformation of Cu, which is also an FCC material with smaller stacking fault energy as compared with aluminum. The results from this study showed that an elongated grain shape microstructure resulted in a dominant C component in simple shear texture, whereas when using equiaxed grain shape, it was not the case (not shown here).…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been a few number of studies investigating the effects of grain shape on texture evolution. Jahedi et al [28] conducted both experiments and the VPSC simulation approach introduced by Beyerlein et al [29] to study systematically the effect of grain shape on texture evolution during simple shear deformation of Cu, which is also an FCC material with smaller stacking fault energy as compared with aluminum. The results from this study showed that an elongated grain shape microstructure resulted in a dominant C component in simple shear texture, whereas when using equiaxed grain shape, it was not the case (not shown here).…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the grains also strongly affects the development of the texture during HPT processing. A typical shear texture is formed when the microstructure is composed of equiaxed grains, while a microstructure with elongated grains leads to the formation of shear texture with a dominance of the C component [160].…”
Section: 122effect Of Initial Grain Sizementioning
confidence: 99%
“…The above model for the critical activation stresses for slip and twin activation has been used in many types of crystal plasticity based modeling technique. For instance, it has been used in homogenization‐based polycrystal plasticity models, such as elasto‐plastic self‐consistent (EPSC) and visco‐plastic self‐consistent (VPSC), as well as within three‐dimensional, spatially resolved techniques, such as crystal plasticity finite element (CPFE) . The EPSC and CPFE models account for elastic deformation in addition to plastic deformation, whereas VPSC only treats plastic deformation.…”
Section: Applicationsmentioning
confidence: 99%